Comparison Between the Effectiveness of Mental Practice and Physical Practice using Cup Stacking on Hand Function in the Elderly - Prasomsri, Jaruwan; Wadbanjerd, Jenjira; Suttinon, Tiriporn; Keereena, Sakongkorn (Journal of Health Science and Medical Research, 2022)
Objective: The objective of this study was to investigate the effect of mental vs. physical cup stacking practice in healthy people aged over 65 years. Material and Methods: Healthy elderly, who met the inclusion criteria, were randomized into 2 groups—physical practice and mental practice. Both groups received cup stacking training according to the specific condition of the group. This study collected data on the immediate effects of the training using the Jebsen Hand Function Test (JHFT) for both hands, the dominant and the non-dominant ones. The movement time during cup stacking and reaction time were measured. The paired t-test and the independent t-test were selected to analyze the differences within and between groups, respectively. Results: There were 39 participants in each group. It was found that the movement time related to stacking cups and the JHFT movement time of the non-dominant hand was significantly lower in the physical practice group compared with the mental practice group. Besides, after training, the movement time for stacking cups and the JHFT movement time of both hands was significantly lower in both groups. However, a statistically nonsignificant result for reaction time was found in the mental practice group after training. Conclusion: This study shows that both mental and physical training can enhance the ability to learn hand movement in the elderly. In further studies, the inclusion of the retention of training effects after practice, a different training approach, and a feedback method should be considered.